Simulink model for planning a new power transmission investment. (February 2014) - Adetona, Sunday; Salawu, Raifu; Okafor, Frank
This paper proposes an Investment Planning Model (IPM) that can be employed in determining the optimal period to inject new investments on some critical sections of any transmission network in the Wholesale Electricity Market in order to sustain its reliability and availability. The mathematical models for realization of the IPM are obtained by capturing the salient effect of increasing Existing Transmission Commitment on Available Transfer Capability. These mathematical models are implemented and executed with the help of embedded Matlab function blocks in the Matlab environment. The input units of the IPM were obtained via the PSAT 2.1.2 software package. In the course of simulations, the proposed IPM was used to predict the investment periods of all the transmission paths of a 14-bus IEEE test system as quickly as possible.